Legionella Becoming a Mutualist: Adaptive Processes Shaping the Genome of Symbiont in the Louse Polyplax serrata - Říhová, Jana (Jihočeská univerzita, 2018)
Genomic modifications coupled with the first known transition of a Legionella bacterium to symbiosis with insects (louse Polyplax serrata). Apart from characteristics typical for other obligatory symbionts in insect (genome reduction), the main innovation of the genome consists in horizontal acquisition of complete biotin operon. Comparative genomic analysis with free living legionellae and other symbiotic bacteria demonstrates convergent evolution of several phylogenetically unrelated louse symbionts.
Legionella Becoming a Mutualist: Adaptive Processes Shaping the Genome of Symbiont in the Louse Polyplax serrata
Keywords: endosymbiont; Legionella polyplacis; Polyplax serrata; horizontal gene transfer; genome evolution; metabolism